PENDAMPINGAN PENCATATAN LAPORAN KEUANGAN DIGITAL PADA UMKM MENGGUNAKAN APLIKASI LAMIKRO - Khoirunnisa, Eka Tri; Wafa, Zaenal (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Training and mentoring are two ways of implementing a community service project aimed at improving the ability of MSMEs to record digital financial reports using the LAMIKRO application. The basis of this community service project is the lack of financial literacy and mastery of digital technology that still makes it difficult for many MSMEs to record and report their financial information. The activity was carried out at the Putra Juwana MSME in Klurak Baru Village, Bokoharjo, Prambanan, Sleman using a participatory method through stages of preparation, socialization, training and technical assistance, as well as evaluation and monitoring. The results of the activity showed that business actors have improved skills in operating the LAMIKRO application and are able to separate personal finances from business. This program has been proven to increase efficiency, data accuracy, and financial transparency and supports the digitalization of MSMEs.